Zur Synonymie von Perissomastix Warren & Rothschild, 1905 (Lepidoptera: Tineidae). - Gozmány, László; Petersen, Günther (Contributions to Entomology = Beiträge zur Entomologie, 1964)
There are discussed the results of a study of type specimens in the collections of the British Museum (Nat. Hist.) London concerning the synonymy of Perissomastix Warren & Rothschild and of two of its species. Nomenclatural Actsintermediella Petersen, 1961 (Catabola), syn. n. of Perissomastix nigriceps Warren & Rothschild, 1905Aphrodoxa Gozmány, 1959 (Tineidae), syn. n. of Perissomastix Warren & Rothschild, 1905Catabola Durrant, 1913 (Tineidae), syn. n. of Perissomastix Warren & Rothschild, 1905Malacyntis Meyrick, 1908 (Tineidae), syn. n. of Perissomastix Warren & Rothschild, 1905